3x+1=(x-9)

Simple and best practice solution for 3x+1=(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+1=(x-9) equation:


Simplifying
3x + 1 = (x + -9)

Reorder the terms:
1 + 3x = (x + -9)

Reorder the terms:
1 + 3x = (-9 + x)

Remove parenthesis around (-9 + x)
1 + 3x = -9 + x

Solving
1 + 3x = -9 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
1 + 3x + -1x = -9 + x + -1x

Combine like terms: 3x + -1x = 2x
1 + 2x = -9 + x + -1x

Combine like terms: x + -1x = 0
1 + 2x = -9 + 0
1 + 2x = -9

Add '-1' to each side of the equation.
1 + -1 + 2x = -9 + -1

Combine like terms: 1 + -1 = 0
0 + 2x = -9 + -1
2x = -9 + -1

Combine like terms: -9 + -1 = -10
2x = -10

Divide each side by '2'.
x = -5

Simplifying
x = -5

See similar equations:

| (2x+3)(2x+5)(x-1)(x-2)=30 | | -10t-2=0 | | -10t^2-2t=0 | | 4x-(3x+7)=-1 | | 2x+3x-2=98 | | 5(4x-6)-8=6x-24 | | 2x^2+9*x-7=0 | | x-22=4 | | x+5+133+x= | | x^3+4x^2+5x+2=0 | | 3(5a-2)-2a+10= | | 3(n-1.8)=2n+1 | | 6(x-1)-2(2-x)=8-(2-6x) | | x^4+4x^3+5x^2+2x=0 | | q*(5-q)= | | 3y=-28-x | | 2(1+x)-1=3(2x+1)+2 | | z-48=-32 | | (5-q)-5q= | | 8x-1/5-1=(50-2x/9)+(3x+3/4) | | 16x+7x+15=0 | | 5-q= | | 10n=4 | | 5x-4=14x-13 | | 3x+26=10x-41 | | 20*(4x+1)-24(3x+1)=15*60-60*(25-x) | | 15x-176=6x-14 | | 24*(3x-1)-20*(5x+1)=120*(x+1)-3*120 | | 6y+(8)(7)-4=42 | | 11x+2=2x+128 | | 155-5x=40x+15x | | 7-10x=55-24x |

Equations solver categories